Pengaruh Leverage, Volume Perdagangan, Ukuran Perusahaan, Profitabilitas, Earning Volatility Terhadap Volatilitas Harga Saham - Ardiansah, Mochamad Ardien; Sugiarto, Sugiarto; Wiratno, Adi; Farida, Yusriyati Nur (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This research aims to analyze and understand the impact of Leverage, stock trading volume, firm size, profitability, and Earning Volatility on stock price volatility. The population of this study consists of technology sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. This research bases its study on the signalling theory. The population of this study consists of technology sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. A total of 63 company data were selected using the purposive sampling method. The data analysis techniques used are descriptive statistical analysis, panel data regression analysis, classical asssumption test, and hypothesis testing with the help of Eviews 12 software. The research results indicate that: (1) Leverage does not affect stock price volatility, (2) Stock trading volume has a positive and significant effect on stock price volatility, (3) Firm size does not affect stock price volatility, (4) Profitability does not affect stock price volatility, and (5) Earning Volatility has a negative and significant effect on stock price volatility.